The Impact Of Fomo And Cyberbullying On Adolescent Mental Health: A Literature Review - Dhita Kurnia Sari; Reni Nurhidayah (Journal of Health Science Community, 2026)
Adolescent mental health has become a growing global concern in the digital era (World Health Organization [WHO], 2021). Increased engagement with social media platforms such as Instagram, TikTok, and Facebook has intensified psychological phenomena including Fear of Missing Out (FOMO) and cyberbullying (Keles et al., 2020; Twenge & Campbell, 2018). This study aims to systematically review and synthesize empirical findings regarding the impact of FOMO and cyberbullying on adolescent mental health. A literature review method was employed using peer-reviewed articles published between 2015 and 2023 indexed in PubMed, Scopus, and Google Scholar. The findings indicate consistent associations between FOMO, cyberbullying victimization, and increased levels of anxiety, depression, stress, low self-esteem, and suicidal ideation (Beyens et al., 2016; Hamm et al., 2015; Kowalski et al., 2014). The interaction between FOMO and cyberbullying may further exacerbate psychological vulnerability among adolescents. The study highlights the importance of digital literacy education, parental involvement, and school-based mental health programs to mitigate these risks.